Tingkat Adopsi Software Akuntansi Cloud-Based pada UMKM dengan Faktor Pendorong dan Penghambat - Sri Ambar Wati; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify the adoption rate of cloud-based accounting software among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, through an evaluation of several factors that drive and hinder its adoption. The method used in this study is a Systematic Literature Review (SLR), which involves obtaining and analyzing published scientific journals from 2021 to 2025 using keywords such as